LL‐37 modulates human neutrophil responses to influenza A virus. Issue 5 (31st July 2014) - Tripathi, Shweta; Verma, Anamika; Kim, Eun‐Jeong; White, Mitchell R.; Hartshorn, Kevan L.
Abstract : LL‐37 upregulates neutrophil respiratory burst and extracellular trap formation in response to influenza A virus, but reduces cytokine generation triggered by the virus. Abstract : Recent studies have shown that the human cathelicidin, LL‐37, has antiviral activity against IAV in vitro and in vivo. Neutrophils are important cellular components of the initial innate response to IAV infection. In addition to its direct antimicrobial activities, LL‐37 has important immunomodulatory effects. In this study, we explore how LL‐37 affects interactions of IAV with human neutrophils. LL‐37 did not alter neutrophil uptake of IAV but significantly increased neutrophil H2 O2 responses to the virus. IAV stimulated production of NETs in vitro, and this response was increased by preincubating the virus with LL‐37. NADPH‐oxidase blockade did not reduce IAV‐induced NET formation or the increased NET response stimulated by LL‐37 + IAV. The increased respiratory burst and NET responses were, however, inhibited by preincubating cells with a formyl peptide receptor blocker, indicating that LL‐37 engages these receptors when complexed with IAV. Responses to IAV alone were not inhibited by formyl peptide receptor blockade. It has been reported that LL‐37 reduces proinflammatory cytokine responses during IAV infection in vivo. We now show that IAV alone potentiated release of IL‐8 from neutrophils, and preincubation with LL‐37 reduced IAV‐stimulated IL‐8 release. These results confirm that LL‐37 modulates human neutrophil responses to IAV in a distinctive manner and could have important bearing on the protective effects of LL‐37 during IAV infection in vivo.